Relevance of Ferroptosis to Cardiotoxicity Caused by Anthracyclines: Mechanisms to Target Treatments - Zhang, Guoxia; Yuan, Chao; Su, Xin; Zhang, Jianzhen; Gokulnath, Priyanka; Vulugundam, Gururaja; Li, Guoping; Yang, Xinyu; An, Na; Liu, Can; Sun, Wanli; Chen, Hengwen; et al. (Frontiers in Cardiovascular Medicine, 2022)
Anthracyclines (ANTs) are a class of anticancer drugs widely used in oncology. However, the clinical application of ANTs is limited by their cardiotoxicity. The mechanisms underlying ANTs-induced cardiotoxicity (AIC) are complicated and involve oxidative stress, inflammation, topoisomerase 2β inhibition, pyroptosis, immunometabolism, autophagy, apoptosis, ferroptosis, etc. Ferroptosis is a new form of regulated cell death (RCD) proposed in 2012, characterized by iron-dependent accumulation of reactive oxygen species (ROS) and lipid peroxidation. An increasing number of studies have found that ferroptosis plays a vital role in the development of AIC. Therefore, we aimed to elaborate on ferroptosis in AIC, especially by doxorubicin (DOX). We first summarize the mechanisms of ferroptosis in terms of oxidation and anti-oxidation systems. Then, we discuss the mechanisms related to ferroptosis caused by DOX, particularly from the perspective of iron metabolism of cardiomyocytes. We also present our research on the prevention and treatment of AIC based on ferroptosis. Finally, we enumerate our views on the development of drugs targeting ferroptosis in this emerging field.